Exon-18-EGFR Mutated Transformed Small-Cell Lung Cancer: A Case Report and Literature Review - Nunzio Digiacomo; Tommaso De Pas; Giovanna Rossi; Paola Bossi; Erika Stucchi; Fabio Conforti; Emilia Cocorocchio; Daniele Laszlo; Laura Pala; Emma Zattarin; Chiara Catania (Current Oncology, 2023)
Small-cell lung cancer (SCLC) transformation from EGFR mutant adenocarcinoma is a rare entity that is considered to be a new phenotype of SCLC. While transformation from adenocarcinoma (ADC) with EGFR exon 19 deletions and exon 21 L858R point mutations has been described, to our knowledge, no cases of transformation to SCLC from exon-18-mutated ADC have been reported. We reported a clinical case of a patient with exon-18-EGFR-transformed SCLC, and we performed a systematic review of the literature.